Hydrocolloids reduce nasal injuries in infants receiving CPAP: a systematic review - Siti Nur Ngaisah; Yeni Rustinah (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2021)
Background: CPAP is the standard oxygenation management in the respiratory emergencies in infants, complications such as nose injuries are still common. Recognizing risk factors and reducing the pressure which created between the adhesive interface and the nasal skin surface can prevent this complicationObjectives: The aims of this literature review is to determine the benefits of hydrocolloid dressing on nasal injury and comfort in infants with CPAP.Methods: Systematic review, the articles search involved several online databases based on the PICO framework and focused on using PRISMA.Results: 9 articles found according to the criteria. There are 3 main themes such as risk factors, the type of interface and  barriers skinConclusions: nasal injury can be prevented by selecting the right interface and administering hydrocolloid as a barrier to reduces pressure at the interface.